APPLICATION OF MULTI FACTOR EVALUATION PROCESS (MFEP) METHOD FOR THE SELECTION OF BUILDING MATERIAL SUPPLIERS ON MAHAKARYA SUKRI PERKASA (MSP) CIREBON - Erwin Sudrajat Rubiyanto; Faisal Akbar; Mohammad Fahlevvi (Jurnal Teknik Informatika (Jutif), 2023)
The property sector is growing along with the increasing need for housing by people in Indonesia. Mahakarya Sukri Perkasa (MSP), is one of the companies engaged in property and housing development. Supplier selection is one of the essential aspects that ensure the smooth operation of the company. From January to May 2021, MSP received 10 consumer complaints from 60 housing development units. Consumers complained that the housing that had been built and occupied suffered damage to certain parts after several months of use. One of the causes of damage is that the quality of the building materials used is not good. This happens because when choosing a supplier for the purchase of building materials, the MSP decides on the cheapest price list of goods. If consumer complaints increase continuously, it will of course result in a decrease in the level of consumer confidence which will reduce MSP income. MSPs need a decision support system that can produce detailed supplier recommendations. The calculation method used in this study is MFEP (Multi-Factor Evaluation Process). There are 5 assessment criteria used, namely price, quality, the diversity offered, supplier response, and delivery time. The results of highest Weight Evaluation test results are 0.86 obtained by Cirebon Mega Bangunan (CMB) with an initial weight of 0.6 price factors, quality 1, the diversity offered 1, supplier response 1, and delivery time 0.6.